The Influence of Discovery Learning on Mathematics Learning Motivation in Elementary Schools - Oktaria, Sesmita; Ain, Siti Quratul (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to analyze the effect of the Discovery Learning approach on students’ motivation in learning mathematics. The research employed a quantitative pre-experimental method with a one-group pretest–posttest design. The subjects were 30 third-grade students selected through purposive sampling. The instrument used was a motivation questionnaire, consisting of 15 items tested for validity and reliability, all of which met the required standards (Cronbach’s Alpha = 0.853). Data analysis included normality, linearity, and paired sample t-tests. The findings show that students’ average motivation score increased by 20.433 points, with a significance value of 0.000 (p < 0.05). These results indicate that Discovery Learning has a significant and positive effect on students’ mathematics learning motivation.